2019
DOI: 10.1002/cncr.32178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of daratumumab, pomalidomide, and dexamethasone in patients with relapsed or refractory myeloma: Utility of re‐treatment with daratumumab among refractory patients

Abstract: BACKGROUND:The efficacy of daratumumab (DARA) both as a monotherapy and in combination with standard-of-care regimens in multiple myeloma (MM) has been established in clinical trials. This article presents a retrospective analysis of the safety and efficacy of DARA in combination with pomalidomide (POM) and dexamethasone (ie, daratumumab, pomalidomide, and dexamethasone [DARA-POM-D]) and, more importantly, the long-term follow-up of a cohort that was naive to DARA and POM as well as a cohort in which the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 29 publications
12
59
0
2
Order By: Relevance
“…Our observations are in line with those reported by Nooka et al (). In their hands, the ORR with DaraPd was 36·8% in patients with Dara or Pom‐refractory disease and 33·3% for those with Dara and Pom‐refractory disease (Nooka et al , ). This would support the hypothesis that the DaraPd combination has the potential to overcome resistance to the individual agents, at least in some cases.…”
Section: Response To Daratumumab Pomalidomide and Dexamethasonesupporting
confidence: 94%
“…Our observations are in line with those reported by Nooka et al (). In their hands, the ORR with DaraPd was 36·8% in patients with Dara or Pom‐refractory disease and 33·3% for those with Dara and Pom‐refractory disease (Nooka et al , ). This would support the hypothesis that the DaraPd combination has the potential to overcome resistance to the individual agents, at least in some cases.…”
Section: Response To Daratumumab Pomalidomide and Dexamethasonesupporting
confidence: 94%
“…Other grade 3 or higher hematologic AEs of interest were anemia and thrombocytopenia, which were observed in 32% and 24% of the patients, respectively. Most importantly, this analysis has demonstrated that even in patients who are refractory to both daratumumab and pomalidomide as individual lines of therapy, the combination can be reused to recapture responses, as evidenced by the ORR of nearly 35% in this cohort of daratumumab‐ and pomalidomide‐refractory patients . A phase 3 randomized study of DPd versus Pd (APOLLO; NCT03180736) for patients with relapsed/refractory multiple myeloma is ongoing (Table ).…”
Section: Daratumumab In Combination With Imids In Patients With Relapmentioning
confidence: 97%
“…Our group at Emory evaluated the efficacy of the DPd regimen in heavily pretreated patients with relapsed/refractory multiple myeloma. This analysis reviewed the utility of retreatment with daratumumab among daratumumab‐refractory patients . A subgroup of 12 patients in cohort 2 (cohort 3) were daratumumab‐ and pomalidomide‐refractory.…”
Section: Daratumumab In Combination With Imids In Patients With Relapmentioning
confidence: 99%
See 1 more Smart Citation
“…An ORR of 57.5% was noted in 40 double-refractory patients. Retrospective data from Emory University Hospital using this combination have also been presented 40. In 19 daratumumab- and pomalidomide-naïve patients with a median of three prior lines of treatment, they reported an ORR of 89%.…”
Section: Efficacy and Safety Of Daratumumabmentioning
confidence: 99%